Pengembangan Bahan Ajar Ekonomi Berbasis Mobile Untuk Meningkatkan Motivasi Belajar Siswa Di Masa Pandemi Covid-19 - Muh Fahrurrozi; Mispandi Mispandi; Muhamad Juaini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This development was carried out to develop mobile-based Economics Teaching Materials to increase student learning motivation during the pandemic. The development model in this study uses the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The research instrument used consisted of: (1) Media Validation Sheet, (2) Material Validation Sheet, (3) Student Motivation Assessment Sheet, (4) Student Initial Needs Assessment Sheet. Validity data consists of validation assessment data from media experts and material experts who are analyzed and by converting the data scores into qualitative data. Effectiveness data was analyzed from the results of the assessment of the motivational instrument which was analyzed by determining the number of scores according to students and then determining the percentage of the total effectiveness based on the absolute assessment. The test results show that the mobile-based class XI economics teaching materials for increasing student learning motivation during the pandemic meet the valid and effective criteria. The validity criteria can be seen from the analysis results of media validity of 90.71% and material validity of 92.5% so that the two validation results meet the valid criteria. The criteria for effectiveness can be seen from the results of the analysis of the motivational instrument. Interest in the appearance and ease of understanding the material independently at home reached a value of 91.7% - 95.8%, indicating that interest in learning in using mobile-based economic teaching materials can be increased by innovative teaching materials that are interesting and easy to operate independently. So when viewed from the motivational instrument, it shows an average presentation of 92% from the standard > 87.50% so that the teaching materials are included in the category of very effective use in online learning during the pandemic